Penerapan Sistem Absensi Online Berbasis Android (Studi Kasus Pada Kantor Pemerintah Daerah Kabupaten Majalengka Jawa Barat) - Safuan Safuan; Deni Rahman (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2021)
The attendance system is very important for assessing employee performance, especially in terms of employee discipline and responsibility. Android-based online attendance applications are starting to be frequently used by companies, because employee loyalty and performance are difficult to measure if the attendance system used by the company still uses a manual attendance system. The purpose of this study is to determine the Android-based online attendance system at the Regional Government Office of Majalengka Regency, West Java. The method used in this research uses a qualitative case study approach. The results showed that the online attendance system based on android can improve the discipline and responsibilities of civil servants in the Regional Government Office of Majalengka Regency, West Java.